Unraveling the effect of Gd doping on the structural, optical, and magnetic properties of ZnO based diluted magnetic semiconductor nanorods. Issue 57 (16th October 2019) - Obeid, Mohammed M.; Jappor, Hamad R.; Al-Marzoki, Kutaiba; Al-Hydary, Imad Ali; Edrees, Shaker J.; Shukur, Majid M.
Abstract : Gd doped ZnO nanorods. Abstract : The structural, magnetic, and optical properties of the pristine and Gd-doped ZnO nanorods (NRs), prepared by facile thermal decomposition, have been studied using a combination of experimental and density functional theory (DFT) with Hubbard U correction approaches. The XRD patterns demonstrate the single-phase wurtzite structure of the pristine and doped ZnO. The rod-like shape of the nanoparticles has been examined by FESEM and TEM techniques. Elemental compositions of the pure and doped samples were identified by EDX measurement. Due to the Burstein–Moss shift, the optical band gaps of the doped samples have been widened compared to pristine ZnO. The PL spectra show the presence of complex defects. Room temperature magnetic properties have been measured using VSM and revealed the coexistence of paramagnetic and weak ferromagnetic ordering in Gd 3+ doped ZnO-NRs. The magnetic moment was increased upon addition of more Gd ions into the ZnO host lattice. The DFT+U calculations confirm that the presence of vacancy-complexes has a significant effect on the structural, electronic, and magnetic properties of a pristine ZnO system.